Widely tunable all-fiber SESAM mode-locked Ytterbium laser with a linear cavity. (1st July 2017) - Zou, Feng; Wang, Zhaokun; Wang, Ziwei; Bai, Yang; Li, Qiurui; Zhou, Jun
Abstract: We present a widely tunable all-fiber mode-locked laser based on semiconductor saturable absorber mirror (SESAM) with a linear cavity design. An easy-to-use tunable bandpass filter based on thin film cavity technology is employed to tune the wavelength. By tuning the filter and adjusting the polarization controller, mode-locked operation can be achieved over the range of 1023 nm–1060 nm. With the polarization controller settled, mode-locked operation can be preserved and the wavelength can be continuously tuned from 1030 nm to 1053 nm. At 1030 nm, the laser delivers 9.6 mw average output power with 15.4 ps 10.96 MHz pulses at fundamental mode-locked operation. Highlights: A tunable all-fiber SESAM mode-locked laser with a linear cavity is presented. The laser delivers 9.6 mw output power with 15.4 ps 10.96 MHz pulses. 37 nm tuning range is obtained by adjust the tunable filter. 20 nm continuous tuning range is obtained without interrupting pulsed operation.